Corpus-Based Discourse Analysis Tools: A Comparative Study of AntConc and Praaline - Asrorova , Nargiza (The Lingua Spectrum, 2025)
Corpus-based discourse analysis has recently garnered importance as a methodological approach in applied linguistics, especially, in discourse studies. The integration of specialized software tools significantly enhances the systematic investigation of discourse in large corpora. This paper provides a comparative analysis of two widely used corpus analysis tools – AntConc and Praaline (an extension of Praat), and gives a descriptive overview of both programs. The comparison aims to shed light into the affordances of both tools for researchers engaged in CBDA of speech. The comparative study focuses on the functions, applications, strengths, and limitations of AntConc and Praaline in the context of spoken discourse analysis. Through an in-depth investigation, it is argued that while AntConc excels in textual concordance and keyword analysis, Praaline enables more nuanced multimodal analysis, particularly of phonetic and prosodic features. Moreover, the paper explores how these tools support diverse research needs, from pedagogical applications to sociolinguistic and pragmatic investigations, making them essential assets in modern linguistic inquiry.